2011
DOI: 10.1088/1674-1056/20/5/054205
|View full text |Cite
|
Sign up to set email alerts
|

Surface second-harmonic generation based on periodically poled LiNbO 3 nonlinear optical crystal

Abstract: We have generated a second-harmonic generation (SHG) of a Q-switched microchip Nd:YAG laser on the surface of a periodically poled LiNbO 3 (PPLN) nonlinear crystal near the grazing incidence angle. Three individual SHG waves as transmitted homogeneous, inhomogeneous and reflected radiations have been generated and their intensities are measured and characterized within a desirable range of about 10 different incidence angles of the Nd:YAG laser as pump source on the PPLN surface. The basic of surface nonlinear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Hence, the SHG usually arises from the surface of metal nanoparticles, where centrosymmetry is broken. [13] Compared to the linear response, it has been experimentally demonstrated that SHG is more sensitive to the metal nanostructure shape. [14] We have already investigated the SHG of centrosymmetric dielectric nanoshperes excited by tightly focused linearly polarized beams [15] or cylindrical vector beams [16] in the frame of the nonlinear Rayleigh-Gans-Debye (RGD) theory [17] when the incident field is not significantly perturbed by particles of low refractive index contrast.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the SHG usually arises from the surface of metal nanoparticles, where centrosymmetry is broken. [13] Compared to the linear response, it has been experimentally demonstrated that SHG is more sensitive to the metal nanostructure shape. [14] We have already investigated the SHG of centrosymmetric dielectric nanoshperes excited by tightly focused linearly polarized beams [15] or cylindrical vector beams [16] in the frame of the nonlinear Rayleigh-Gans-Debye (RGD) theory [17] when the incident field is not significantly perturbed by particles of low refractive index contrast.…”
Section: Introductionmentioning
confidence: 99%